KAJIAN LITERATUR PENGARUH MEDIA VISUAL TERHADAP PENGETAHUAN GIZI DAN ASUPAN ZAT GIZI MAKRO PADA ANAK SEKOLAH - Sindi Febrianti; Suaebah; Nopriantini; Nurrizky Natasha Gunawan (Media Gizi Khatulistiwa, 2024)
Background: School children are a human resource (HR) in the future as the nation's next generation whose potential and quality still need to be improved. Elementary school children are also one of the groups that are prone to experiencing malnutrition, the cause is a low economic level and unbalanced food intake and low parental knowledge. One of the factors causing nutritional problems in school-age children includes insufficient nutritional intake and insufficient nutritional knowledge. Objective: The research objective was to examine some of the research results with journals on the effect of visual media on nutritional knowledge and intake of macro nutrients in school children. Method: This type of research is a literature review which aims to analy ze journals in the form of nutritional knowledge and intake of macro nutrients in school children through visual media. With the limit of journal publication from 2009 to 2019, it consists of national and international journals. There are 14 journals used as material for literature review, which have themes related to writing topics or variables. Results:  The results of the literature review that have been carried out show that there is an increase in the average knowledge after being given visual media with an increase in the difference of 13.9. In addition, based on the results of the statistical test studied, it shows that there are differences in the average knowledge before and after being given visual media. The difference in knowledge difference between the visual media used has the highest result in comic media, namely 16. On carbohydrate nutrient intake with the difference increase after being given poster media (67.7) and comics (1.7). And the statistical results show that there is a difference in the average value before and after, but in the comic media, the statistical results show that there is no difference in the average value before and after. The intake of energy, protein and fat nutrients shows that the difference in the increase after being given poster and ppt media is decreasing, but in the protein intake using comic media with an increase in the difference there is an increase (16.7). And the results of statistical tests show that there is no significant difference using poster media on protein and fat intake. Suggestion : In this literature review, it is suggested that further research is expected to create visual media for nutrition education to school children related to nutritional intake by controlling the intake of food consumed, so that the factors that most influence the increase and decrease in nutritional intake of school children and to strengthen previous studies.